Factores familiares y rendimiento escolar en alumnos del primer grado de secundaria. I.E. Nº 80407 Gonzalo Ugás Salcedo, Pacasmayo, 2020 - Loje Alva, Mirella Anali (2023)
This thesis was carried out with the objective of determining the influence of family factors on school performance in first grade students of secondary level, Pacasmayo 2020. The type of applied research has been considered, based on an explanatory design, and the sample consisted of 30 students between women and men, with whom we worked applying the methods and techniques of quantitative research: Statistical method and as a technique to the survey, and qualitative research: inductive - deductive method; and as technique the interview. This research was based on analyzing and explaining the family factors that influence school performance, because the teaching and learning process have various aspects such as the family climate. For this reason, the influence of a good family climate is essential, which gives rise to a positive and affective educational climate that is more stimulating and motivating that transcends the school activities of the students. Likewise, in order to contribute to good school performance, it is important to create spaces for a good family climate, communication, and trust between students and their families that make it possible to combat the problem and strengthen educational action. This thesis is subdivided into: I. Introduction: Problematic reality, background, theoretical bases and conceptual framework; II. Materials and methods; III. Results presentation; IV. Discussion of results. V. Conclusions; SAW. Bibliographic references and Annexes.